El teatro y su incidencia en el desarrollo cognitivo de niños de 4 años - Ortiz Corozo, Ana Bertha (2024)
The objective of this research project is to analyze the impact of theater on the cognitive development of 4-year-old children, in addition to evaluating the level of cognitive development of 4-year-old children at the Cerro Azul Private School. For this reason, the behavior of the students in the development or development of their skills within the classroom is considered. In this context, the research approach is mixed: it is quantitative because the data from the surveys carried out with the teachers are analyzed, and qualitative because an observation sheet is applied to assess the children's achieved and unachieved skills. On the other hand, the type of research is descriptive because the advantages and impact of theater on cognitive development are mentioned, and the most important aspects of cognitive development and its importance are also pointed out. In context, the problem lies in the lack of attention, the difficulty in resolving conflict, the poor understanding of the basic concepts of time and the poor expression of emotions....